The 5 love languages of children the secret to loving children effectively - Chapman, Gary D 1938-; Campbell, Ross 1936- (Chicago Northfield Publishing, 2016)
"More than 1 million sold! You know you love your child. But how can you make sure your child knows it? The #1 New York Times bestselling The 5 Love Languages
"More than 1 million sold! You know you love your child. But how can you show it so they really feel loved? The #1 New York Times bestselling The 5 Love Languages
Includes bibliographical references
1
Keywords: Child psychology; EDUCATION / Elementary; FAMILY & RELATIONSHIPS / Life Stages / School Age; FAMILY & RELATIONSHIPS / Parenting / General; Interpersonal communication in children; Parent and child